Combinatorial Approaches for Efficient Design of Photoswitchable Protein-Protein Interactions as In Vivo Actuators - Zhang, Xiao; Pan, Yuxin; Kang, Shoukai; Gu, Liangcai (Frontiers in Bioengineering and Biotechnology, 2022)
Light switchable two-component protein dimerization systems offer versatile manipulation and dissection of cellular events in living systems. Over the past 20 years, the field has been driven by the discovery of new conformation switchable photoreceptors, the engineering of conformation-selective binder proteins, and the development of photoactivatable compounds as dimerization inducers. This perspective is to categorize designs of photoswitchable protein heterodimerization systems, compare their advantages and limitations, and bridge them to different applications. Our goal is to identify unmet needs in the current implementation and highlight recent technical advances that might address long-standing challenges.